On Dating and Attribution of the 13th Century Icon ‘The Mother of God Eleousa’ from a Private Collection / К вопросу о датировке и атрибуции иконы «Богоматерь Умиление» XIII века из частного собрания - Maria Yakovleva / Мария Игоревна Яковлева (Визуальная теология)
The paper examines some iconographic and stylistic features of the panel with the Virgin Eleousa from a private collection, exhibited at the Mikhail Abramov Museum of Russian Icons in October 2023 – February 2024. An exquisite artistic language of the icon indicates that the painter skillfully used typical Byzantine techniques. However, some undoubtedly italianizing intonations are also evident. Thus, closest analogies to somewhat amorphous facial features of the Virgin can be found in Italian panels of the mid-13th century. Broad, fleshy faces of the angels, depicted in medallions on either side of the Virgin’s halo, are endowed with almost sensual expressiveness. They demonstrate closeness to some works of Italian art dated back to the second half of the 13th – early 14th centuries. Considering painter’s virtuoso mastery of the entire arsenal of Byzantine art, presence of Western elements should be explained by the influence of a mixed Latin-Greek cultural environment. The Sicilian origin of the panel seems most plausible. A number of icons and mosaics preserved in Sicily from the 13th to the early 14th centuries reveal close stylistic similarities with the works of Constantinopolitan art. Their attribution raises significant difficulties: they could have been created either by visiting Byzantine masters or by their local disciples – Greeks or Italians. Icon’s classicizing style retains only a faint echo of late Comnenian mannerism. Calmness of refined draperies, rounded volumes and, especially, facial types give us every reason to date the panel approximately to the middle of the 13th century. В исследовании рассматриваются некоторые иконографические и стилистические особенности иконы «Богоматерь Умиление» из частного собрания, экспонировавшейся в Музее русской иконы имени Михаила Абрамова в октябре 2023 – феврале 2024 года. Рафинированный художественный язык памятника свидетельствует о том, что исполнивший его живописец органично владел приёмами византийского изобразительного искусства. Иконе присущи, однако, и несомненные итальянизирующие интонации. Так, ближайшие аналогии несколько аморфному рисунку лика Богоматери могут быть найдены в итальянских станковых произведениях середины XIII столетия. Широкие полнокровные лики ангелов, представленных в медальонах по обе стороны от нимба Марии, наделены почти чувственной выразительностью и демонстрируют близость некоторым византинизирующим итальянским произведениям второй половины XIII – раннего XIV вв. Принимая во внимание тот факт, что мастер виртуозно владеет всем арсеналом формальных приёмов византийской живописи, присутствие отдельных западных элементов должно объясняться созданием иконы в смешанной греко-латинской культурной среде. Наиболее вероятным кажется предположение о её сицилийском происхождении. Ряд памятников, сохранившихся на Сицилии от XIII – начала XIV вв., обнаруживает стилистическую близость константинопольским произведениям, поэтому их атрибуция вызывает существенные затруднения: они могли создаваться как приезжими византийскими мастерами, так и их местными учениками – греками или италийцами. Классицизирующий стиль иконы сохраняет лишь лёгкие отголоски экспрессии позднекомниновского маньеризма, а успокоенная отточенность драпировок, круглящаяся объёмность форм и, в особенности, типы ликов дают все основания для её датировки временем около середины XIII века.